The Factors Effectiveness of Driving License Service Procedures - Arnia Jovi; Umar Ma'ruf; Latifah Hanim; Rakhmat Bowo Suharto (Jurnal Daulat Hukum, 2022)
The purpose of this study is to find out, examine and analyze what factors affect the ineffectiveness of the service procedure for making a driving license at the SIM issuance unit. In this paper, the author uses a normative juridical method with research specifications in the form of descriptive analysis. Based on the discussion, it is concluded that the assessment of the effectiveness of the service procedure for making a driving license is determined by 4 (four) indicators, namely resources, funds, facilities and infrastructure; the quantity and quality of the goods/services to be produced has been determined; service time limit; and service procedures. With the available resources, Satpas SIM Satlantas feel able to carry out SIM making services effectively. In the Satpas SIM Satlantas Polres environment, the SIM fee has been adjusted to the applicable regulations, namely PP RI No. 60 of 2016 concerning Types and Tariffs of Non-Tax State Revenue and is very firm for the prevention and prosecution of illegal levies from persons with indications of extortion within the Satpas SIM Satlantas environment. In addition, nowadays the issue of police operational funds has indeed become a polemic throughout Indonesia